Estimation of mean water vapour residence time during tropical cyclones using a Lagrangian approach - Albenis Pérez-Alarcón; Patricia Coll-Hidalgo; José C. Fernández-Alvarez; Raquel Nieto; Luis Gimeno (Tropical Cyclone Research and Review, 2022)
Tropical cyclone (TC)-related rainfall mostly depends on the atmospheric moisture uptake from local and remote sources. In this study, the mean water vapour residence time (MWVRT) was computed for precipitation related to TCs in each basin and on a global scale by applying a Lagrangian moisture source diagnostic method. According to our results, the highest MWVRT was found for the TCs over the South Indian Ocean and South Pacific Ocean basins (∼3.08 days), followed by the Western North Pacific Ocean, Central and East North Pacific Ocean, North Indian Ocean, and North Atlantic Ocean basins (which exhibited values of 2.98, 2.94, 2.85, and 2.72 days, respectively). We also found a statistically significant (p < 0.05) decrease in MWVRT, at a rate of ∼2.4 h/decade in the North Indian Ocean and ∼1.0 h/decade in the remaining basins. On average, the MWVRT decreased during the 24 h before TCs made landfall, and the atmospheric parcels precipitated faster after evaporation when TCs moved over land than over the ocean. Further research should focus on the relationship between global warming and MWVRT of atmospheric parcels that precipitate over TC positions.